Fostering Girl Child Education in Malawi - Mzumara, Cecilia (Luviri Press, 2019)
Cover -- Copyright page -- Title page -- Dedication -- Acknowledgements -- General Introduction -- Foreword by Bishop Joseph Mkasa Zuza -- Foreword by Sr. Huguette Ostiguy MIC -- ABBREVIATIONS AND ACRONYMS -- Contents -- Chapter One - Introduction -- Chapter Two - The Missionary Sisters of the Immaculate Conception -- MIC Sisters on the African Continent -- MIC Sisters in Nyasaland (Malawi) -- MIC Sisters' Sectors of Evangelization -- Challenges Encountered by the Pioneering Sisters -- Conclusion -- Chapter Three - Establishment of Marymount Secondary School -- The Pioneering Stage: 1956-1973 -- Funding -- The Development of Marymount -- The School Library -- Academic Programmes -- Extra-Curricular Activities -- Prominent Visitors to Marymount -- Exposure to Political Functions -- The Consolidation Period (1973-1992) -- Conclusion -- Chapter Four - FromGrant-Aided to Private -- Factors for Privatization -- A Rebirth of Marymount -- Church-State Relationship on Educational Matters -- Advantages of Privatization -- Challenges -- Conclusion -- Chapter Five - Marymount 2000 - 2010 -- MIC Sisters' Involvement -- The 40th Anniversary of the School -- School Awards -- Human and Material Development of the School -- Teacher-Pupil Relationship -- Major challenges -- Conclusion -- Chapter Six: The Specific Contribution of MIC Sisters to Girl Child Education -- School Ethos -- Change in Mental Framework -- Role Models -- Character Formation -- Cultural Transformation -- Human, Spiritual and Christian Formation -- Senior Positions in Society -- The Foundation of the Sisters of the Holy Rosary -- Current Activities of MIC Sisters in Mzuzu Diocese -- Conclusion -- Chapter Seven: Suggestions and Recommendations -- Major Findings -- Suggestions and Recommendations -- Conclusion -- Bibliography -- Back cover.